Experimental investigation and modelling on air layer formation around a rotating grinding wheel. Issue 1 (31st December 2016) - Majumdar, Sujit; Banerjee, Ahin; Das, Santanu; Chakroborty, Samik
Abstract: Impingement of grinding fluid deep into grinding zone is a challenge due to presence of air layer around the grinding wheel. This paper presents experimental observation on air boundary layer formed around a rotating grinding wheel, a rexine-cloth covered grinding wheel and a solid disc. The effect of porous and rough grinding wheel surface towards strengthening air boundary layer has been studied. Modelling has been done to estimate variation of air pressure within this boundary layer. Out of three different methods of extrapolation done, the most suitable one is suggested. Results obtained using three different wheels are compared. A scraper board is also employed to observe reduction of air pressure. Higher value of air pressure is noted in case of bare grinding wheel than that in other conditions. Use of scraper board along with rexine-covered wheel is found to reduce air pressure to a large extent such that it becomes close to air pressure noted around the solid wheel. It shows the beneficial effect of using scraper board and rexine-pasted wheel to suppress air layer effectively. Correspondingly, grinding fluid is expected to reach deep into the grinding zone thereby rendering better control of grinding temperature, and hence, better grinding performance.